(untitled) (Environment & Health, 2018)
Objective: We analyzed the levels of the risk for the health of the population, living in a zone of the impact of thermal power objects at the substantiation of the sizes of sanitary-and-protective zones. Materials and methods: For the study we chose the coal-fired thermal power plant in the Kiev oblast. Determination of the control points depended on the meteorological and topographic peculiarities of the studied territory that affected the character of the spatial dissemination of the pollutants in ambient air on the boundary of residential building (at the distances from 400 to 11000 m).For the calculation of averaged concentrations (annual, monthly, daily) we used the ISC-AERMOD software complex. The calculation of risk criteria was carried out according to adopted procedure of risk assessment, recommended by the US Environmental Protection Agency and the World Health Organization. Results: The inhomogenity of the spatial pollution of ambient air of the TEP on the boundary of residential building from the emissions of the foreground pollutants (sulfur dioxide; nitrogen dioxide; carbon oxide; dust, undifferentiated by the composition (DUC); PM 10) is demonstrated. The levels of non-carcinogenic risk for the health of the population (at daily exposure) were established to be exceeded only for dust, undifferentiated by the composition (DUC) and PM 10 (HQ=1.1÷2.5). Additional calculations of the levels of the individual risk of the death of PM10 were performed. Those levels fluctuated at studied territories: IRМ = 3,6×10-5 ÷ 7,7×10-4 and were inadmissible for the residence of the population in 17 control points. Obtained results confirm a necessity for the monitoring investigations for PM10 and PM 2.5 in atmospheric surface layer in a zone of the impact of TPP in order to develop the environmental protective and preventive measures at the substantiation of the sizes of sanitary-and-protective zones. Сonclusions: Performed investigations prove “a hypothesis” on the correlation between long (chronic) exposure of the population with fine dust at spatial dissemination for long distances (over 4000 m) and probability of additional mortality. It requires the substantiation at the determination of sanitary-and-protective zones for thermal power objects, taking into account a specificity of spatial dissemination of the pollutants in the atmospheric surface layer, stipulated by the meteorological and topographic peculiarities of studied territory.As to the planning of measures for the reduction of risk levels in this case, they should be based on the results of more thorough evaluation of different aspects of existing problems and determination of the degree of their priority on the basis of the "benefit-harm" analysis.